Analisis Perhitungan Struktur Gedung Asrama MAN I Tanjung Pura, Kabupaten Langkat Menggunakan Software SAP 2000 - Rokiyah, Rokiyah; Hermansyah, Hermansyah; Nurmaidah, Nurmaidah (Universitas Medan Area, 2025)
This article aims to analyze the structure of the building of Madrasah Aliyah Negeri I Tanjung Pura Dormitory, Langkat Regency using SAP 2000 software to obtain fast and accurate calculations, and compare the results of the calculation of column reinforcement, beams, slabs, and foundations with planning consultants. The calculation results show the dimensions and reinforcement as follows: Column K1 (40x40 cm) uses 8D22mm, K2 (30x30 cm) uses 8D16mm, beam B1 (25x50 cm) T8D16mm, L9D16mm, beam B2 (25x60 cm) T8D16mm, L7D16mm, beam B3 (20x40 cm) T6D16mm, L7D16mm, and beam BA (20x30 cm) T5D16mm, L5D16mm. Roof slabs (10 cm thick) and floor slabs (12 cm thick) use ø10-200mm and ø10-150mm reinforcement. The pilecap foundation uses D16-200mm reinforcement for X and Y directions. The results of SAP 2000 analysis show that the reinforcement is up to 50% larger than that of consultants, due to differences in assumptions related to economics and ease of implementation in the field.